Fabrication of ethosuximide loaded alginate/polyethylene oxide scaffolds for epilepsy research using 3D-printing method - Karabulut, Hatice; Dutta, Abir; Moukbil, Yunis; Cisen Akyol, Aysim; Ulag, Songul; Aydin, Banu; Gulhan, Rezzan; Us, Zeynep; Kalaskar, Deepak M.; Gunduz, Oguzhan (Frontiers in Bioengineering and Biotechnology, 2023)
Epilepsy is a medical condition that causes seizures and impairs the mental and physical activities of patients. Unfortunately, over one-third of patients do not receive adequate relief from oral Antiepileptic Drugs (AEDs) and continue to experience seizures. In addition to that, long term usage of AEDs can cause a range of side effects. To overcome this problem, the precision of 3D printing technology is combined with the controlled release capabilities of biodegradable polymers, allowing for tailored and localized AED delivery to specific seizure sites. As a result of this novel technique, therapeutic outcomes can be enhanced, side effects of AEDs are minimized, and patient-specific dosage forms can be created.. This study focused on the use of ethosuximide, an antiepileptic drug, at different concentrations (10, 13, and 15 mg) loaded into 3D-printed sodium alginate and polyethylene oxide scaffolds. The scaffolds contained varying concentrations (0.25%, 0.50%, and 0.75% w/v) and had varying pores created by 3D patterning sizes from 159.86 ± 19.9 µm to 240.29 ± 10.7 µm to optimize the releasing system for an intracranial administration. The addition of PEO changed the Tg and Tm temperatures from 65 oC to 69 oC and from 262 oC to 267 oC, respectively. Cytotoxicity assays using the human neuroblastoma cell line (SH-SY5Y) showed that cell metabolic activity reached 130% after 168 hours, allowing the cells to develop into mature neural cells. In vitro testing demonstrated sustained ethosuximide release lasting two hours despite crosslinking with 3% CaCl2. The workpaves the way for the use of ethosuximide -loaded scaffolds for treating epilepsy.